Effect of curing time on the strain at break of heat cured acrylic resin. - Islam, Kazi Ziaul; Khan, Md Ali Afzal (Update Dental College Journal, 2014)
Objectives: The aim of this study was to find out the effect of curing time on the strain at break of heat cured acrylic resin (1) cured at 1000c with time difference. Methods : In this study , 60 heat cured acrylic resin samples were processed with compression moulding technique at 1000c among which each of 20 samples were cured for 20, 40 and 60 minutes separately. Strain at break of heat cured acrylic resin were determined by using the Universal Testing Machine(4) with the help of QMAT software in computer. Results : The ANOVA result showed that there was no significant differences among the groups with respect to the strain at break of heat cured acrylic resin. The p- value of strain at break of heat cured acrylic resin is 0.590. The mean strain at break of heat cured acrylic resin cured at 1000c for 20 minutes was 3.5458% , 40 minutes was 3.4195 % , 60 minutes was 3.3187 % and standard deviation respectively 0.4158 % , 3.8640 % , 0.3902 %. Conclusion : The strain at break of heat cured acrylic resin cured at 1000c for different period of time ( at 20 , 40 & 60 minutes ) have given no significant differences. DOI: http://dx.doi.org/10.3329/updcj.v3i2.17993 Update Dent. Coll. j: 2013; 3 (2): 09-12